Comparing Immature Development and Life History Traits in Two Coexisting Host-Feeding Parasitoids, Diglyphus isaea and Neochrysocharis formosa (Hymenoptera: Eulophidae) - Yi-bo ZHANG; Shu-long LU; Wan-xue LIU; Wen-xia WANG; Wei WANG; Fang-hao WAN (Journal of Integrative Agriculture, 2014)
Coexisting natural enemies that share a common host resource in the same guild usually exhibit variation in their life history traits, due to their need to share a similar ecological niche. In this study, we compared the immature development times and adult life history traits of two coexisting, host-feeding parasitoids, Diglyphus isaea Walker and Neochrysocharis formosa Westwood (Hymenoptera: Eulophidae), of which both attack larvae of the same agromyzid leafminers. These two species are both synovigenic, idiobiont parasitoids, whose adults consume host fluids (“host feeding”) and lay anhydropic eggs. Of the two, D. isaea has a larger body but little or no initial egg load, and engages in similar lifetime host-feeding events. However, it achieves higher fecundity, longer adult longevity, and higher host suppression ability than N. formosa, which has a smaller body and higher initial egg load. Although D. isaea engages in similar lifetime host-feeding events with N. formosa, all of its gains in life history traits per host-feeding event of D. isaea were larger than those of N. formosa. The age-specific fecundity and host mortality curves of N. formosa were more skewed in early life than those of D. isaea. In addition, the ovigeny index of N. formosa was negatively correlated to body size. Our results confirmed that two coexisting parasitoids, which share the same host resource, show different immature development patterns and life history traits, suggesting that different resource allocation mode could be a general rule of coexisting species sharing the same habitat or host.